Phytofabrication, characterization of silver nanoparticles using Hippophae rhamnoides berries extract and their biological activities - Rana, Neha; Banu, A. Najitha; Kumar, Bimlesh; Singh, Sandeep K.; Abdel-razik, Noha E.; Jalal, Naif A.; Bantun, Farkad; Vamanu, Emanuel; Singh, Mahendra P. (Frontiers in Microbiology, 2024)
Fabrication of plant-based metal nanoparticles has yielded promising results, establishing this approach as viable, sustainable, and non-toxic in the biomedical sector for targeted drug delivery, diagnostic imaging, biosensing, cancer therapy, and antimicrobial treatments. The present work demonstrates the suitability of Hippophae rhamnoides berries for the instant green synthesis of silver nanoparticles to check their antioxidant, lipid peroxidation, and antimicrobial potential. The preliminary characterization of Hippophae rhamnoides-mediated AgNPs was validated by monitoring the color shift in the solution from pale yellow to reddish brown, which was further confirmed by UV-vis spectroscopy and the plasmon peaks were observed at 450 nm. Field Emission Scanning Electron Microscopy (FESEM) and X-ray diffraction (XRD) were used to evaluate the surface topography and structure of AgNPs. The results revealed that the AgNPs were spherical in shape with an average size distribution within the range of 23.5 -28nm and a crystalline structure. Negative zeta potential (-19.7 mV) revealed the physical stability of synthesized AgNPs as the repulsive force to immediate aggregation. The bioactive functional moieties involved in reducing bulk AgNO3 into AgNPs were further validated by FTIR. Total antioxidant potential was calculated by the DPPH free radical scavenging method revealing its dose-dependent activity. TBARS (Thiobarbituric acid reactive species) was adapted to test lipid peroxidation, and Hippophae rhamnoides-mediated AgNPs showed a 79% inhibition in lipid peroxidation compared to Hippophae rhamnoides berries extract as 65%. Furthermore, the antibacterial tests showed 37 ± 0.01 mm and 35 ± 0.0132 mm, zones of inhibition against E. coli MTCC1698 and S. aureus MTCC 3160 with MIC and MBC values of 1mg/mL respectively. This research suggests that AgNPs have promising future applications in biomedicine and as drug delivery systems.